The Determinants of Earnings Management in Manufacturing Companies Listed on the Indonesia Stock Exchange - Bhegawati, Desak Ayu Sriary; Rustiarini, Ni Wayan; Widyantari, Ida Ayu Putu Surya; Made Ariandini, Ida Ayu; Listya Dewi, Ni Kadek (AIBPM Publisher, 2024)
Benefit control is an issue in an association that begins from the fighting of the importance between the proprietor and the director. Powerless oversight and following withinside the association will simplify it for supervisors to play out the income control. In this manner, an organization administration system is needed to regulate the acts of profit control. This investigation focuses to check and accomplish observational verification of the effect of organization length, institutional possession, fair-minded officials, and the leading group of directors on profit control. The general population on this examination are creation organizations listed at the Indonesia Stock Exchange withinside the 2021-2023 period. Assurance of the example of the utilization of purposive inspecting approach and got upwards of 42 examples of creating organizations. The old-style presumption investigation, the integrity of the sound investigation, and more than one direct relapse assessment are the reality evaluation methods used. The effects confirmed that fair magistrates, a leading body of managers, and changeable institutional possession had little bearing on profit control. Organizational length and review of advisory group characteristics afterward have a horrifying impact on income control.